Exequatur of the divorce judicial decision of the marriage of husband or wife as a condition to exercise the right to family reunification? The relevant legal doctrine of the Spanish Supreme Court of 2022 - Adroher Biosca, Salomé (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
In this paper, I analyze the right to family reunification of divorced and remarried foreigners from Islamic countries, in the light of two recent and important Supreme Court decisions. The Court has established legal doctrine affirming the unnecessary exequatur of the divorce decree of the first marriage to prove that the second marriage is not polygamous in the face of the visa application and residence permit for family reunification.